Penjualan Objek Jaminan Tanpa Persetujuan Debitur Dalam Perjanjian Utang Piutang Ditinjau dari Hukum Perjanjian dan Hukum Jaminan - Liu, Anisya Rua Ratu; Suparto, Susilowati; Wiyono, Sridewi Anggraeni (Media Hukum Indonesia (MHI), 2024)
The life of a person or company is inseparable from debt and credit transactions with the background of fulfilling a daily need. Business entities or people in conducting lending and borrowing activities that provide loan services, do not want the money loaned to just disappear without a reciprocal relationship between the borrower and the provider of funds. In fact, generally borrowers can pledge goods or assets owned as collateral if one day they cannot redeem or fulfil their obligations. Collateral that is sold without the consent of the owner can have legal consequences on the sale and ownership of the collateral. The purpose of this research is to examine and determine the legal status of ownership collateral objects sold by creditors to other parties without the consent of the debtor in a debt and credit agreement, as well as the creditor’s responsibility to the debtor who owns the collateral as the injured party from the sale of the collateral object without the debtor’s consent in terms of agreement law and collateral law. The research method used is using a normative juridical approach by using research result, works of legal experts, and library material that use secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials. The results showed that the legal status of ownership of the object of collateral obtained by unlawful acts from the sale and purchase of collateral object that are being encumbered by debt and credit guarantees is declared legally invalid and ownership remains according to the Certificate of Title, namely the debtor in the debt and credit agreement as the owner of the land. The creditor’s responsibility towards the debtor as the injured party in the sale of the collateral object in the debt agreement is to provide immaterial compensation in the form of returning and surrendering land ownership by the land buyer to the land owner, namely the debtor in the debt and credit agreement as well as a statement from the judge’s decision that the creditor has committed an unlawful act by selling the land that is being encumbered by collateral.